Cognitive correlates of women's postpartum depression risk and symptoms: the contribution of dysfunctional beliefs and negative thoughts. (1st November 2020) - Fonseca, Ana; Canavarro, Maria Cristina
Abstract: Background: Despite the extensive research on interpersonal and clinical risk factors for postpartum depression (PPD), there is a paucity of research on the potential role of cognitive variables (dysfunctional beliefs and negative thoughts) as correlates of PPD symptoms. Aims: This exploratory study aimed to understand the cognitive processes of women at a higher risk (i.e. presenting well-established interpersonal and clinical risk factors) for PPD by: (a) comparing women's dysfunctional motherhood-related beliefs and frequency of automatic thoughts, as a function of their levels of PPD risk and symptoms; (b) examining the cognitive correlates of PPD symptoms, controlling for the presence of well-established risk factors. Method: A cross-sectional internet survey comprising 441 postpartum women was conducted. Results: Women presenting high-risk for PPD showed more dysfunctional motherhood-related attitudes ( p < 0.001), more frequent negative thoughts ( p < 0.001) and less frequent positive thoughts ( p < 0.001) than low-risk women. More dysfunctional beliefs related to maternal responsibility, more frequent negative thoughts related with personal maladjustment and with the metacognitive appraisal of the thoughts' content, and less frequent positive thoughts were found to be significantly associated with PPD symptoms. Conclusion: The inclusion of cognitive variables in risk assessment and preventive efforts for PPD may hold potential to increase its clinical efficacy.